Ensayo de reconstrucción virtual de un túmulo funerario: El túmulo del Mortórum (Cabanes, Castellón) - Jose Luján Valderrama; Gustau Aguilella Arzo (Virtual Archaeology Review)
We presents a virtual reconstruction of the megalithic tomb found near of Tossal del Mortórum (Cabanes, Castellón) dated on the second millennium BC. The structure discovered in 2005 was plundered at an undetermined moment, and their conservation status is very precarious. Given the undoubted interest of the tomb, located in an area of the peninsula with little evidence of megalithism, we decided to make a essay of its virtual reconstruction. The basic software used in the modeling and rendering is Blender 2.56, so this paper can also show the capabilities of open source software for these projects.